Estimation of cancer burden in Guangdong Province, China in 2009. Issue 3 (December 2015) - Cao, Su-Mei; Xu, Yan-Jun; Lin, Guo-Zhen; Huang, Qi-Hong; Wei, Kuang-Rong; Xie, Shang-Hang; Liu, Qing
Abstract Background Surveying regional cancer incidence and mortality provides significant data that can assist in making health policy for local areas; however, the province- and region-based cancer burden in China is seldom reported. In this study, we estimated cancer incidence and mortality in Guangdong Province, China and presented basic information for making policies related to health resource allocation and disease control. Methods A log-linear model was used to calculate the sex-, age-, and registry-specific ratios of incidence to mortality (I/M) based on cancer registry data from Guangzhou, Zhongshan, and Sihui between 2004 and 2008. The cancer incidences in 2009 were then estimated according to representative I/M ratios and the mortality records from eight death surveillance sites in Guangdong Province. The cancer incidences in each city were estimated by the corresponding sex- and age-specific incidences from cancer registries or death surveillance sites in each area. Finally, the total and region-based cancer incidences and mortalities for the entire population of Guangdong Province were summarized. Results The estimated I/M ratios in Guangzhou (3.658), Zhongshan (2.153), and Sihui (1.527) were significantly different (P < 0.001), with an average I/M ratio of 2.446. Significant differences in the estimated I/M ratios were observed between distinct age groups and the three cancer registries. The estimated I/M ratio in females was significantly higher than that in males (2.864 vs. 2.027, P < 0.001). It was estimated that there were 163, 376 new cancer cases (99, 689 males and 63, 687 females) in 2009; it was further estimated that 115, 049 people (75, 054 males and 39, 995 females) died from cancer in Guangdong Province in 2009. The estimated crude and age-standardized rate of incidences (ASRI) in Guangdong Province were 231.34 and 246.87 per 100, 000 males, respectively, and 156.98 and 163.57 per 100, 000 females, respectively. The estimated crude and age-standardized rate of mortalities (ASRM) in Guangdong Province were 174.17 and 187.46 per 100, 000 males, respectively, and 98.59 and 102.00 per 100, 000 females, respectively. In comparison with the western area and the northern mountain area, higher ASRI and ASRM were recorded in the Pearl River Delta area and the eastern area in both males and females. Conclusions Cancer imposes a heavy disease burden, and cancer patterns are unevenly distributed throughout Guangdong Province. More health resources should be allocated to cancer control, especially in the western and northern mountain areas.